Phase II study of an AKT inhibitor MK2206 in patients with relapsed or refractory lymphoma. (27th July 2015) - Oki, Yasuhiro; Fanale, Michelle; Romaguera, Jorge; Fayad, Luis; Fowler, Nathan; Copeland, Amanda; Samaniego, Felipe; Kwak, Larry W.; Neelapu, Sattva; Wang, Michael; Feng, Lei; Younes, Anas
Summary: We conducted a phase II study of the AKT inhibitor, MK2206 in patients with relapsed or refractory lymphoma of any histology excluding Burkitt lymphoma or lymphoblastic lymphoma. MK‐2206 was administered orally at 200 mg once weekly in 28‐d cycles up to 12 cycles in the absence of progression or significant toxicity. The dose was adjusted based on tolerance. A total of 59 patients were enrolled. The final doses patients received were 300 mg ( n = 33), 250 mg ( n = 2), 200 mg ( n = 16) and 135 mg ( n = 8). Based on intent‐to‐treat analysis, objective response was observed in 8 (14%) patients (2 complete response and 6 partial response), with median response duration of 5·8 months. The overall response rate was 20% in 25 patients with classical Hodgkin lymphoma. Rash was the most common toxicity (any grade 53%, Grade 3 in 15%) and was observed in a dose‐dependent manner. The correlative cytokine analysis showed paradoxical increase in several cytokines, which may be explained by negative feedback mechanism induced by the on‐target effect of AKT inhibitor. Our data demonstrate that MK2206 has a favourable safety profile with a modest activity in patients with relapsed Hodgkin lymphoma. The future studies should explore mechanism‐based combinations (clinicaltrials.gov NCT01258998).